IMMUNOMODULATORY EFFECTS OF ETHANOL EXTRACT OF CURCUMA MANGGA RHIZOMES IN MICE - Yuandani; Suwarso, Edy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was conducted to evaluate the immunomodulatory effects of ethanol extract of Curcuma mangga by in vivo study. Methods: The ethanol extract of C. mangga was comprised to carbon clearance method for its immunomodulatory potential. The extract wasadministered orally at doses of 100, 200, and 400 mg/kg BW to mice for 7 days. On day 8, carbon ink was injected, and the blood was collected formeasurement of elimination of carbon. Total leukocyte count was also determined. Results: The evaluation of immunomodulatory potential of ethanol extract of C. mangga revealed a dose-dependent increase in phagocytosis ability.The phagocytic index of ethanol extract of C. mangga was more than those of negative control, indicating the immunostimulatory activity of C. mangga.It showed low stimulation on total leukocyte count.Conclusion: The results indicate that ethanol extract of C. mangga rhizomes possesses immunomodulatory activity and has therapeutic potential forthe treatment of infectious diseases.